Actual issues on legal status of a space object - Рибачок, Вікторія Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
For a long time space law was considered only as a branch of public international law, however, with the development of economic relations in the late 20th century commercialization of space activities occurred, which led to the fact that there was an urgent need for improving legal regulation of civil turnover of such a specific object, for civil legal relations as a space object, since the rules of public international law regulate private legal relations in no way. Scientific approaches concerning the definition of a space object are directed to combine in the notion of a space object each of the characteristics typical of media that explores space and objects of civil turnover that may be the subject of the related transactions. The only legislative definition of such concept as "a space object" is contained in the Convention on international liability for damage caused by space objects, dated September 01, 1972, entered into force on 16 October 1973 for Ukraine and the Convention on registration of objects launched into outer space dated September 15, 1976, became effective on September 14, 1977 for Ukraine, however, the definition contained in these Conventions (component parts of a space object, its delivery system and parts thereof) contains a tautology and does not allow to unambiguously determine which objects can be related to be space ones. Current Ukrainian legislation does not contain a definition of a space object that can be used in civil legal relations, and also leaves outside the attention the legal framework of these objects. Determining the legal status of a space object we can conclude that the optimal approach is that which exists in the legislation of the Russian Federation, since the Civil code of the Russian Federation extends the regime of real estate on space objects, not setting them equal to real estate, as provided in the Civil code of the Republic of Belarus, and not referring them to movables, as evidenced by the analysis of the current legislation of Ukraine. The distribution of real estate regime to space objects is primarily due to the fact that these objects are of great importance for the state and the state should control their civil turnover. To treat space objects as immovable property is also impractical, since these objects do not have main feature of property, inherent in all legal systems – inseparability from the land without damage to the latter.